Late gestation under‐ and overnutrition have differential impacts when combined with a post‐natal obesogenic diet on glucose–lactate–insulin adaptations during metabolic challenges in adolescent sheep. (13th October 2014) - Khanal, P.; Axel, A. M. D.; Kongsted, A. H.; Husted, S. V.; Johnsen, L.; Pandey, D.; Pedersen, K. L.; Birtwistle, M.; Markussen, B.; Kadarmideen, H. N.; Nielsen, M. O.
Abstract Aim To determine whether late gestation under‐ and overnutrition programme metabolic plasticity in a similar way, and whether metabolic responses to an obesogenic diet in early post‐natal life depend on the foetal nutrition history. Methods In a 3 × 2 factorial design, twin‐pregnant ewes were for the last 6 weeks of gestation (term = 147 days) assigned to HIGH (N = 13; 150 and 110% of energy and protein requirements, respectively), NORM (N = 9; 100% of requirements) or LOW (N = 14; 50% of requirements) diets. The twin offspring were raised on high‐carbohydrate–high‐fat (HCHF; N = 35) or conventional (CONV; N = 35) diets from 3 days to 6 months of age (around puberty). Then intravenous glucose (GTT; overnight fasted), insulin (ITT; fed) and propionate (gluconeogenetic precursor; PTT; both fed and fasted) tolerance tests were conducted to evaluate (hepatic) metabolic plasticity. Results Prenatal malnutrition differentially impacted adaptations of particularly plasma lactate followed by glucose, cholesterol and insulin. This was most clearly expressed during PTT in fasted lambs and much less during ITT and GTT. In fasted lambs, propionate induced more dramatic increases in lactate than glucose, and HIGH lambs became more hyperglycaemic, hyperlactataemic and secreted less insulin compared to the hypercholesterolaemic LOW lambs. Propionate‐induced insulin secretion was virtually abolished in fasted HCHF lambs, but upregulated in fasted compared to fed CONV lambs. HCHF lambs had the greatest glucose‐induced insulin secretory responses. Conclusion Prenatal malnutrition differentially programmed glucose–lactate metabolic pathways and cholesterol homeostasis. Prenatal overnutrition predisposed for hyperglycaemia and hyperlactataemia, whereas undernutrition predisposed for hypercholesterolaemia upon exposure to an obesogenic diet. Prenatal overnutrition (not undernutrition) interfered with pancreatic insulin secretion by non‐glucose‐dependent mechanisms.